Mobile communications technology, tools, applications, authentication, and security : IFIP World Conference on Mobile Communications 2-6 September 1996, Canberra, Australia - Encarnacao, Jose Luis; Rabaey, Jan M. (Chapman & Hall, 1996)
Mobile computing is one of the biggest issues of computer technology, science and industry today. This book looks at the requirements of developing mobile computing systems and the challenges they pose to computer designers. It examines the requirements of mobile computing hardware, infrastructure and communications services. Information security and the data protection aspects of design are considered, together with telecommunications facilities for linking up to the worldwide computer infrastructure. The book also considers the mobility of computer users versus the portability of the equipment. The text also examines current applications of mobile computing in the public sector and future innovative applications.